Odpowiedź :
Szczegółowe wyjaśnienie:
3a(2b+4)+2a(3-5b)= 6ab + 12a + 6a -10ab= -4ab +18a
-2x(5x-y)-x(8x-2y)= -10x²+ 2xy -8x² +2xy= -18x²+4xy
5p(2+3r-p)-3p(2p-4)= 10p +15pr -5p²-6p² + 12p= -11p²+ 22p +15pr
3k(4-m+2k)-3m(2-3k)= 12k - 3km+6k² -6m + 9mk= 6k²+6km+12k - 6m
b) (2a+6)(3a+5)= 6a²+ 10a + 18a + 30= 6a²+ 28a + 30
(3p-2)(5p+4)= 15p² + 12p -10p- 8= 15p²+ 2p - 8
(2x-3)(5x-1)= 10x²+ 2x -15x+3= 10x² -13x+3
(3y--2)(4-3y)= 12y- 9y² -8+6y= -9y² + 18y -8
c) x(3x+6)+(x-4)(2x+1) = 3x²+6x + 2x²+x -8x -4= 5x² -x -4
2a(5a-3)-(2a+3)(a+4)= 10a² -6a -2a²-8a -3a -12= 8a²-17a-12
(3u-2)(2u-1) -5u(2u+3)= 6u²- 3u -4u +2 -10u²-15u= -4u²-22u +2
(3y-5)(2y+3)-3y(5-2y)= 6y² + 9y -10y -15 -15y + 6y² = 12y²- 16y -15
Zobacz więcej na Brainly.pl - https://brainly.pl/zadanie/15312508#readmore
Odpowiedź:
A) 3(2b-1) + 4(1-b)= 6b - 3 + 4 - 4b = 2b + 1
B) 5(3-2a) -(4a+6) *3= 15 - 10a - 12a - 18 = -3 - 22a
C) (a+7)(b-2)= ab - 2a + 7b - 14
D) (2x-3)(5-b)= 10x - 2bx - 15 + 3b
E) 3x+2x*5x - 7x^2+ 3x^2= 3x + 10x² - 7x² + 3x²= 3x + 6x²
F) -4b*5a+2a*5-3a*2b+4ab= -20a + 10a - 6ab + 4ab = -10a - 2a
Szczegółowe wyjaśnienie:
Mam nadzieję, że pomogłam